Understanding of stoichiometry by learners from Form Four to final year of general secondary education in Cameroon - Ateba, Jeremie Awomo; Woukeng, Josephine Nita Tematio; Nchia, Lawrence Ntam; Bouni, Ayina (European Scientific Journal, ESJ, 2025)
The aim of the present research is to determine the conceptions of learners from Form Four to Upper Sixth (13-19 years) of general secondary education in Cameroon about the concept of stoichiometry. A preliminary analysis of the didactic transposition of the concept of chemical reaction in the Form Four textbook, combined with an epistemological study of the concept of stoichiometry, enabled us to design an 8-item paper-and-pencil questionnaire. The questionnaire was administered to 239 learners ranging from four to Upper Sixth students of five general secondary schools. The data collected were analyzed using Dehon’s (2018) significance level model. The results show that many students assign irrelevant meanings to the concepts within the conceptual network of stoichiometry. For instance, 54.4% of students conceive of the stoichiometric coefficient at the macroscopic level as a quantity of matter. Furthermore, only 20.4% of students correctly determine the number of molecules (or atoms) of one reactant needed to react completely with a known number of molecules (or atoms) of another reactant, and 36.8% correctly determine the quantity of matter of one reactant required to react completely with a precise quantity of another reactant. It appears that stoichiometry is better conceptualized by students at the macroscopic level than at the microscopic level.